2021
DOI: 10.3390/app11135954
|View full text |Cite
|
Sign up to set email alerts
|

Diamond-Shaped Extended Fins for Heat Transfer Enhancement in a Double-Pipe Heat Exchanger: An Innovative Design

Abstract: Heat transfer enhancement in heat exchangers results in thermal efficiency and energy saving. In double-pipe heat exchangers (DPHEs), extended or augmented fins in the annulus of the two concentric pipes, i.e., at the outer surface of the inner pipe, are used to extend the surface of contact for enhancing heat transfer. In this article, an innovative diamond-shaped design of extended fins is proposed for DPHEs. This type of fin is considered for the first time in the design of DPHEs. The triangular-shaped and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Zhu et al [35] performed a numerical investigation on fluid parameters and their impact on heat transfer, and the study concluded that a reduced fluid velocity improves the thickness of the thermal boundary layer. Ishaq et al [36] studied the effect of flow distribution on the performance of a double pipe heat exchanger when adding fins of a diamond shape. Based on the present brief literature review, it could be concluded that the non-uniformity has a significant effect on the heat transfer performance of heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [35] performed a numerical investigation on fluid parameters and their impact on heat transfer, and the study concluded that a reduced fluid velocity improves the thickness of the thermal boundary layer. Ishaq et al [36] studied the effect of flow distribution on the performance of a double pipe heat exchanger when adding fins of a diamond shape. Based on the present brief literature review, it could be concluded that the non-uniformity has a significant effect on the heat transfer performance of heat exchangers.…”
Section: Introductionmentioning
confidence: 99%